Anthropological retribution for inevitable progress - Soghomonyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
From the second half of the 20th century, people have become disillusioned with the ideology of "progressivism". A non-self-determined “one-dimensional person” is being formed, who blindly follows social stereotypes and conventions, living with demonstrative activity. The highest value of the consumer society and the motivation for the activity of "one man" is pleasure. Homelessness, that is alienation, becomes the doom of this world. Homelessness, perceived in this sense, means inauthenticity, a reduction of human existence to the mythical, to the “society of the spectacle,” where the transcendental integrity of life is lost.   Analyzing the system of values, actions and behavior of the "one-dimensional person" of the "society of the spectacle", the author comes to the conclusion that in order not to be on the "borderline of time", it is necessary to start a conservative revolution, so that the highest spiritual orientation of a person is not the progress, but an eternal return, or, more precisely, a return to the eternal, a return to the all-embracing integrity of life.
Keywords: progressivism; crisis; uncertainty; alienation; homelessness; society of spectacle; man-manipulator; one-dimensional man; anthropological crisis; return to the eternal